Piceatannol Prevents Colon Cancer Progression via Dual‐Targeting to M2‐Polarized Tumor‐Associated Macrophages and the TGF‐β1 Positive Feedback Signaling Pathway. Issue 15 (15th June 2022) - Chiou, Yi‐Shiou; Lan, Yi‐Ming; Lee, Pei‐Sheng; Lin, Qianyu; Nagabhushanam, Kalyanam; Ho, Chi‐Tang; Pan, Min‐Hsiung
Abstract : Scope: M2 phenotype tumor‐associated macrophages (M2‐TAMs) play a key role in distant metastasis and poor clinical outcomes. Herein, a specific molecular mechanism that contributes to malignant progression is illuminated and investigates whether piceatannol (PIC) can target the crosstalk between M2‐TAMs and cancer cells for potential colorectal cancer (CRC) therapy. Methods and results: To mimic the tumor microenvironment (TME), direct and indirect coculture systems in vitro and in vivo mouse xenograft models are established. The results demonstrate that post‐treatment with PIC in TME more effectively prevented the aggressive features and stemness of SW480 cells by restricting the polarization of M2‐like macrophages and blocking the transforming growth factor β1 (TGF‐β1) positive feedback autocrine/paracrine loop that exists between M2‐like polarized macrophages and cancer cells. Furthermore, xenograft assays also observe significant repression in tumor growth and lung metastases with the administration of PIC. The key mechanism underlying the antimetastasis effects of PIC may include its directly inhibitory activity against TGF‐β receptor type‐1 (TGF‐βR1) in the M2‐like TAMs‐created TME. Conclusion: These novel findings demonstrate that PIC is a potent TGF‐β1/TGF‐βR1 pathway inhibitor and TME modulator for preventing tumor progression and metastasis in CRC by reeducating TAMs. Abstract : Schematic illustration of the M2‐like tumor‐associated macrophages (TAMs)‐created tumor microenvironment (TME) in SW480 cells and the proposed mechanism of the effects of piceatannol (PIC) on the TGF‐β1/TGF‐βR1 positive feedback autocrine/paracrine loop signaling pathways.